Effective Functionalization of Carbon Nanotubes for Bisphenol F Epoxy Matrix Composites (2012)
ABSTRACT: A brand-new type of multifunctional nanocomposites with high DC conductivity and enhanced mechanical strength was fabricated. Ionic liquid functionalized Carbon Nanotubes (CNTs-IL) were embedded into epoxy matrix with covalent bonding by the attached epoxy groups. The highest DC conductivity was 8.38 × 10–3 S.m–1 with 1.0 wt. (%) loading of CNTs-IL and the tensile strength was increased by 36.4% only at a 0.5 wt. (%) concentration. A mixing solvent was used to disperse CNTs-IL in the epoxy monomer. The dispersion and distribution of CNTs-IL in the polymer matrix were measured by utilizing both optical microscopy and scanning electron microscopy, respectively